Biomechanical evaluation of pedicle screw stability after 360-degree turnback from full insertion: effects of screw shape, pilot hole profile and bone density - Li, Yun-Da; Hsieh, Ming-Kai; Chen, Weng-Pin; Lee, De-Mei; Tsai, Tsung-Ting; Lai, Po-Liang; Tai, Ching-Lung (Frontiers in Bioengineering and Biotechnology, 2023)
Intraoperative pedicle screw depth adjustment after initial insertion, including both forward and backward adjustments, is sometimes necessary to facilitate rod application and ensure that the screw is in the correct position, which is determined by intraoperative fluoroscopy. Adjusting the screw with forward turns has no negative influence on the screw fixation stability; however, screw turnback may weaken the fixation stability. The aim of this study is to evaluate the biomechanical properties of screw turnback and demonstrate the reduction in the fixation stability after the screw is turned 360 degrees from its full insertion position. Commercially available synthetic closed-cell polyurethane foams with three different densities simulating various degrees of bone density were utilized as substitutes for human bone. Two different screw shapes (cylindrical and conical) together with two different pilot hole profiles (cylindrical and conical) were tested. Following specimen preparation, screw pullout tests were conducted using a material test machine. The mean maximal pullout strength between full insertion and 360-degree turnback from full insertion in each setting was statistically analyzed. The mean maximal pullout strength after 360-degree turnback from full insertion was generally lower than that at full insertion. The reduced mean maximal pullout strength after turnback increased with decreasing bone density. Conical screws had significantly lower pullout strength after 360-degree turnback than cylindrical screws. The mean maximal pullout strength was reduced by up to approximately 27% after 360-degree turnback when using a conical screw in a low bone density specimen. Additionally, specimens treated with a conical pilot hole presented a less reduction in pullout strength after screw turnback as compared to those with a cylindrical pilot hole. The strength of our study was that we systematically investigated the effects of various bone densities and screw shapes on screw stability after turnback, which has rarely been reported in the literature. Our study suggests that pedicle screw turnback after full insertion should be reduced in spinal surgeries, particularly procedures that use conical screws in osteoporotic bone. Pedicle screw secured with a conical pilot hole might be beneficial for screw adjustment.